2010
DOI: 10.1039/b916497a
|View full text |Cite
|
Sign up to set email alerts
|

Soluble, folded and active subtilisin in a protic ionic liquid

Abstract: The activity of proteases chymotrypsin and subtilisin dissolved in a range of protic hydroxylalkylammonium ionic liquids was tested against the model substrate APEE (N-acetyl-L-phenylalanine ethyl ester); activity was only observed for subtilisin in diethanolammonium chloride (DEA Cl), while chymotrypsin was not active in any PIL tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
(16 reference statements)
0
21
0
Order By: Relevance
“…The subtilisin retained activity in diethanolammonium chloride with a lower rate than the aqueous buffer, but higher than in hexane. 397 No activity was observed for any of the other PILs, or with the other protease of chymotrypsin. In contrast, the aprotic IL of BMIm PF 6 supported activity of chymotrypsin but not subtilisin.…”
Section: Biocatalysismentioning
confidence: 96%
See 2 more Smart Citations
“…The subtilisin retained activity in diethanolammonium chloride with a lower rate than the aqueous buffer, but higher than in hexane. 397 No activity was observed for any of the other PILs, or with the other protease of chymotrypsin. In contrast, the aprotic IL of BMIm PF 6 supported activity of chymotrypsin but not subtilisin.…”
Section: Biocatalysismentioning
confidence: 96%
“…396 The activity and structure of the enzymes subtilisin and chymotrypsin were tested using a model substrate in six hydroxyl containing PILs, which had water concentrations typical for "dry" PILs. 397 The PILs used were diethanolammonium chloride or methanesulfonate, dimethylethanolammonium acetate or glycolate, bis(2-methoxyethyl)ammonium sulfamate, and N-butyldiethanolammonium trifluoromethanesulfonate. The subtilisin retained activity in diethanolammonium chloride with a lower rate than the aqueous buffer, but higher than in hexane.…”
Section: Biocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Not only the ammoniumbased ILs were helpful in preventing it from self-aggregation nevertheless, it also proved to be useful in controlling the thermal instability of the protein. 112 An exceptional example of enzyme catalysis in low-water system was focussed by Falcioni et al 82 Subtilisin was found to be active in DEACl which was surprising since PILs containing chloride anion was considered to be detrimental for the activity of enzymes. 82 The probable reason for this typical behaviour was hypothesized to be coordination of the two cation hydroxyls to chloride which overcomes the denaturing capability of chloride anion.…”
Section: The Effects Of Ammonium-based Ils On the Activity And Stabilmentioning
confidence: 99%
“…Bmim][PF 6 ]) using N-acetyl-L-phenyl-alanine ethyl ester (APEE) as the substrate was carried out by Falcioni et al82 On contrary to the expectation, CT was found to be inactive in all studied ILs. However, surprisingly it maintained some of the activity in[Bmim][PF6 ].The misfolding/unfolding of CT in DEACl was assumed to be the reason of loss in activity.…”
mentioning
confidence: 99%